STRATEGI KOMUNIKASI PENANGANAN PEMINDAHAN PASAR TIBAN DI KOTA PEKALONGAN - Trimanah, Trimanah; Mubarok, Mubarok (BAPPEDA Kota Pekalongan, 2014)
Pekalongan is one of the citiesin Indonesia that undergo arapid development in various fields. One of thestands out economic activity of the town is Pasar Tiban. Pasar Tiban is a term used for a traditional market which opened without any legal approval from the local government. Based on the data taken from Disperindagkop and UMKM Pekalongan, there are 28 pasar tiban spread across the city in 2014. Eventhough it is ilegal, somehow it moves the informal sector of the city. However,its development has caused social problems such astraffic jam, disorder, anddiscomfort. Its existencehas violatedthe ActNo.22of 2009 on Traffic and Transportation (LLAJ Law), Article number 275 paragraph (1) in conjunction with Article 28 paragraph (2), and Act No. 22 of 2009, which regulates the use of the road and side walk. In- depth research has to be done in order to findthe best solutionto overcomethe phenomenonof Pasar Tiban. The purpose of this study is to create a communication strategy to relocate Pasar Tiban without neglecting the interests of traders and communities. This research was conducted by combining quantitative and qualitative research methods. Quantitative data are obtained from the questionnaire, where as qualitative data are obtained from in-depth interviews as well as field observations. The result showsthe importance of coordination and unity among local leaders, SKPD, and Police so that the relocation can be done without any friction. Although most traders do not agree with therelocation there are some traderswho are willing tobe relocated if the concept and the srtucture if the new area is good enough and able to improve their we lf are. In a communication strategy, theobjectives of an action should be clearly defined so that the traderscould easily accept, understand,and are willing to follow all the stages needed for the relocation. The selected communication strategy includes fourt actics, namely; Interpersonal communication, Organizational media, Newsmedia, Advertising and Promotional Media Tactic. All of them will be running perfectly if the objectives was cleary explanied and full support from the stakeholders. Keyword: Pasar Tiban market, strategy, communication, relocation